Regular poles of local L-functions for GSp(4) with respect to split Bessel models (the subregular cases) - Rösner, Mirko; Weissauer, Rainer (Arxiv, 2018)
Piatetskii-Shapiro has defined local spinor L-factors for infinite-dimensional irreducible representations of GSp(4,k) over a local non-archimedean field k, attached to a choice of a Bessel model. We classify the so-called subregular poles, these are the regular poles that do not come from the asymptotic of the Bessel functions. For anisotropic Bessel models there are no subregular poles.
Gesehen am 25.02.2019